CHARACTERISTIC OF THE CASE OF MUNA LANGUAGE VERBS - La Alu Alu (Journal of Indonesian Language Education and Literary, 2016)
The characteristic of the case of Muna language verbs: (1) the feature of the stative verb argument: (a) the semantic feature of stative verbs [Os], (b) the semantic feature of stative verbs [E], (c) the semantic feature of stative verbs [O—B], and (d) the semantic feature of stative verbs [O—L]; (2) the semantic feature of process verbs the argument of process verbs: (a) the semantic feature of process verbs [O], (b) the semantic feature of process verbs [O—A]; (3) the semantic feature of the argument of action verb: (a) the semantic feature of action verbs [A], (b) the semantic feature of action verbs [O—A], (c) the semantic feature of action verbs [O—K—A], and (d) the semantic feature of action verbs [O—L—A].